Clinical Characteristics of Hydrocephalus Following the Treatment of Pyogenic Ventriculitis Caused by Multi/Extensive Drug-Resistant Gram-Negative Bacilli, Acinetobacter Baumannii, and Klebsiella Pneumoniae - Pandey, Sajan; Yao, Pei Wen; Qian, Zhouqi; Ji, Tao; Wang, Ke; Gao, Liang (Frontiers in Surgery, 2022)
Objective Hydrocephalus is common after ventriculitis. This study explores hydrocephalus's clinical characteristics following pyogenic ventriculitis due to multidrug-resistant and extensively drug-resistant Acinetobacter baumannii and Klebsiella pneumoniae. Patients and Methods We retrospectively reviewed the patients with post-neurosurgical pyogenic ventriculitis due to multidrug-resistant and extensively drug-resistant Acinetobacter baumannii and Klebsiella pneumoniae in our department between Jan 2014 and June 2020. Once diagnosed, patients received intraventricular lavage followed by daily intraventricular administration of Colistin (Polymyxin-E). The patient's clinical/radiographic findings were analyzed and evaluated 6 months after discharge. Results In total, 48 cases were included in this study. 25% were female. The median age was 45 (SD ± 15) years old. Median intraventricular Colistin administration to acquire sterile Cerebrospinal fluid (CSF) was 20 days. Forty-one patients developed hydrocephalus; among them, 18(43%) were multiloculated hydrocephalus (MLH), 23(56%) were uni/non-loculated hydrocephalus (ULH/NLH), and 7(17%) did not develop hydrocephalus. Patients with MLH had (15 days) delayed initiation of intraventricular irrigation p<0.022. They had (32 days) longer intraventricular Colistin p<0.003 and showed worse outcome in terms of Glasgow outcome score (GOS) at six months follow up than those without hydrocephalus. The mean score of the MLH group was 1.67 (SD1.23), and ULH/NLH was 2.61(SD1.4) at p<0,008. Conclusions Multiloculated hydrocephalus is common in patients receiving delayed intraventricular administration of Colistin and required longer duration on intraventricular Colistin to treat pyogenic ventriculitis caused by multidrug/extensive drug-resistant Acinetobacter baumannii and Klebsiella pneumonia. It is associated with worse clinical outcomes.